2019
DOI: 10.1109/jlt.2018.2880361
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time 10 Gbps Polarization Independent Quasicoherent Receiver for NG-PON2 Access Networks

Abstract: In this paper, we propose and test experimentally a real-time 10 Gbps polarization independent quasicoherent receiver for NG-PON2 access networks. The proposed 10 Gbps quasicoherent receiver exhibits a sensitivity of-35.2 dBm after 40 km SSMF transmission with a commercial generic EML as transmitter. This sensitivity means a 14.9 dB improvement over a direct detection scheme with a photodiode after 40 km SSMF transmission. Therefore, the use of the proposed 10 Gbps quasicoherent receiver with the tested EML wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The QC receiver [5,6] consists of an optical coupler combining the LO and the signal, followed by a polarization beam splitter (PBS). After the PBS, the signal and the LO of each polarization are detected with a PD and transimpedance amplifier (TIA) with a combined electrical bandwidth of 39 GHz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The QC receiver [5,6] consists of an optical coupler combining the LO and the signal, followed by a polarization beam splitter (PBS). After the PBS, the signal and the LO of each polarization are detected with a PD and transimpedance amplifier (TIA) with a combined electrical bandwidth of 39 GHz.…”
Section: Methodsmentioning
confidence: 99%
“…A tuneable laser has been selected in the experiment reported here for the ease and repeatability of precise tuning. Previous studies [5,7] have demonstrated the QC receiver to be highly tolerant to laser line width and phase noise -real time operation with VCSEL transmitters and LO has even been shown. This is a consequence of the use of envelope detection which removes the phase information thereby increasing tolerance to phase noise.…”
Section: Methodsmentioning
confidence: 99%
“…Alternative concepts were recently presented with real time implementation and refinements starting from the polarizationindependent receiver introduced by Glance Error [33], for either IM [5] or DPSK signals [12]. Using IM, the RX was successfully implemented till 10 Gb/s, by using analog electronic processing.…”
Section: Figure 10 -Scheme Of the Pi-rx Based On 3x3 Coupler And Ber Curves A) And Eye Diagrams Bc) Taken By The Real Time Rx Implementatmentioning
confidence: 99%
“…In addition, it was proven that the RX proposed in [5] also allows for VCSEL-based transmitters and LO: this feature makes it very promising for low-cost implementation.…”
Section: Figure 10 -Scheme Of the Pi-rx Based On 3x3 Coupler And Ber Curves A) And Eye Diagrams Bc) Taken By The Real Time Rx Implementatmentioning
confidence: 99%
See 1 more Smart Citation